Income, saving and investment of agricultural households: A state and farm level analysis based NAFIS 2016-17 - Bathla, Seema; Kumar, Anjani; Saroj, Sunil; Kumar, Ashutosh; Gupta, Neha (National Bank for Agriculture and Rural Development, India, 2022)
The present study analyses the income, saving and saving gap among agricultural households (HHs) to understand their investment behaviour, using the data obtained from the NABARD All India Rural Financial Inclusion Survey (NAFIS) 2016-17, which was conducted by the National Bank for Agriculture and Rural Development (NABARD). The NAFIS had the crop year 2015-16 (kharif and rabi seasons) as the reference year. It covered more than 40,000 households, of which 55% were agricultural HHs and the remaining were non-agricultural HHs. The sample was drawn from all the states, and covered farmers with different size of land holdings. Direct enquiries were made about HHs income, expenditure on food and non-food items including farm inputs, amount deposited in bank and invested in financial and physical assets, outreach of institutional credit, financial inclusion and so on.